Produktivitas Jamur Merang (Volvariella volvaceae) pada Media Campuran Kulit Singkong dan Jerami Padi yang Ditanam dalam Keranjang dan Baglog - Setyowati, Pratika; , Dra. Suparti, M.Si (2017)
Cassava peel is the residual of cassava tubers processing that contains holocellulose, hemicelluloses, and lignin. That required as growing medium of straw mushroom. The purpose of this study to determine the effect of using mixed media of cassava peel and with different comparison that planted on bassket and baglog based of straw mushroom roductivity. This study was prepared by a mpletelyrandomized design (CRD) with 2 factors and 3 replicates. First factor is comparison of cassava peel and straw (K0) 0g:500g ( as the control), (K1) 125g:375g, (K2) 250g:250g, (K3) 75g:125g, (K4) 500g:0g. Second factor is planting: (U) keranjang, (B) baglog. The parameters measured were the number of fruit bodies and edible mushroom fruit body weight. Data were tested by Two Way Anova. Based on the analysis of variance showed that the addition of different concentrations of cassava peel media by planting in raised keranjang and baglog give effect to the amount of body weight of fruit and mushroom fruit body. The best treatment for body weight of the mushroom fruit is UK2 with 813,33 g, while the lowest treatment BK4 with 66,66 g. The best treatment for a number of fruiting bodies is UK2 with 34,33 fruit body, while the lowest was treated fruit BS4 with 6.00 fruit body